Análisis de las obras literarias de autores ecuatorianos llevados al cine en los últimos 5 años, origen y desarrollo del cine ecuatoriano - Zamora Sánchez, Lourdes Dayana (2021)
The following is a case study that addresses the analysis of the different literary works taken to the cinema, beginnings and development of Ecuadorian cinema. The objective is to identify why a literary work is taken to the cinema, the relevance it has today, and at the same time to determine the beginnings and development of Ecuadorian cinema. In addition, we will identify the problems that exist today in terms of development, quality, universal themes, and screen quotas, the little support that the government has for the arts and culture of our country is worrisome because all this encompasses our history and customs. We will also analyze a result obtained through surveys and interviews that will strengthen our theoretical support, based on public and professional opinions by experts in cinematography. We will conclude that cinema as a means of communication is within the reach of the citizen and is an art, our country is full of imagination, stories rich in information, and the necessary resources to produce feature films, documentaries, cinema, etc. Finally, as a recommendation it is important that topics like this have their place and space in the country, mainly to encourage young people and adults to consume what is ours, so that we have more people interested and motivated to work, direct and produce a film space and not only that, but so that in this way we can expand internationally and address universal themes.